A combined health action process approach and mHealth intervention to reduce workplace sitting time in office-working adults: a secondary analysis examining health-related quality of life and work performance outcomes. Issue 10 (3rd October 2021) - Rollo, Scott; Prapavessis, Harry
Abstract: Objective: This secondary analysis study examined the effects of a 6-week theory-based planning and mHealth text message intervention targeting workplace sitting time on health-related quality of life and work performance in office workers. Design: Office-working adults ( M age =45.18 ± 11.33 years) were randomised into either a planning + text message intervention ( n = 29) or control ( n = 31) condition. Outcome Measures: Workplace sitting time, time spent in specific non-sedentary behaviours (e.g. standing), health-related outcomes (i.e. emotional well-being, energy/fatigue, perceived role limitations), and work performance were assessed at baseline and week 6. Results: Significant group by time interaction effects, that favoured the intervention group, were found for perceived role limitations due to emotional health problems and emotional well-being. No significant interaction effects emerged for energy/fatigue, role limitations due to physical health problems or work performance. Significant correlations in the expected direction were found between sedentary/non-sedentary behaviours and health-related outcomes. No significant mediation effects were found to suggest the intervention affected health-related outcomes through reductions in sedentary behaviour. Conclusion: Reducing workplace sitting improves emotional well-being and contributes to fewer perceived role limitations due to emotional health problems among office workers.